Program Konseling Restrukturisasi Kognitif Untuk Mereduksi Kecenderungan Adiksi Game Online Pada Remaja - Gita Adi Persada; Anne Hafina; Nurhudaya Nurhudaya (Universitas Mathla'ul Anwar Banten, 2017)
Adolescent who got some addiction of online game has negative cognition. The research goal is to know the tendency profile of online game and to describe counseling hypothetic program of restructuration to reduce tendency of online game. This research used descriptive method where the population and sample is students of SMP Negeri 45 Bandung year 2015/2016 that consist of 323 students and the sample is 137 students. Deciding sample used non probability sampling with purposive sampling. The research instrument used questionnaire that point to addiction tendency aspects of online game. The result showed that: 1) generally, the addiction tendency of online game is categorized very low; 2) the result of data processing showed that addiction tendency aspects on mood modification aspect has 10 students is categorized average with percentage of 7,3%; 3) the counseling program plan of cognition restructuration is to reduce addiction tendency of online game on student that focused to reduce some indicator that is categorized low. The recommendation of research is proposed to BK teachers at school and researchers further.